2016
DOI: 10.1371/journal.pone.0147356
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis-Specific IL-21+IFN-γ+CD4+ T Cells Are Regulated by IL-12

Abstract: In the current study of Mycobacterium tuberculosis (MTB)-specific T and B cells, we found that MTB-specific peptides from early secreted antigenic target-6 (ESAT-6) and culture filtrate protein-10 (CFP-10) induced the expression of IL-21 predominantly in CD4+ T cells. A fraction of IL-21-expressing CD4+ T cells simultaneously expressed Th1 cytokines but did not secrete Th2 or Th17 cytokines, suggesting that MTB-specific IL-21-expressing CD4+ T cells were different from Th1, Th2 and Th17 subpopulations. The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…An emerging literature supports that anti-microbial effector CD4 T cells can exhibit mixed Th1- and Tfh-like phenotype and function (Carpio et al, 2015, Li et al, 2016, Nakayamada et al, 2011, Obeng-Adjei et al, 2015, Velu et al, 2016, Wikenheiser et al, 2016). Viral infections are linked to expansion of effector Tfh cells that express CXCR3 and co-produce IFN-γ and IL-21 following experimental SIV infection (Velu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An emerging literature supports that anti-microbial effector CD4 T cells can exhibit mixed Th1- and Tfh-like phenotype and function (Carpio et al, 2015, Li et al, 2016, Nakayamada et al, 2011, Obeng-Adjei et al, 2015, Velu et al, 2016, Wikenheiser et al, 2016). Viral infections are linked to expansion of effector Tfh cells that express CXCR3 and co-produce IFN-γ and IL-21 following experimental SIV infection (Velu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In human Mtb infection, NKT cells from plural fluids of tuberculosis patients produce IL-21 to help B cells to secrete IgG and IgA (18), pulmonary tuberculosis patients have less circulating IL-21 levels (19) and IL-21 regulates Mtb specific IFN-γ+CD4+ T cell responses (35) suggesting a role for IL-21 in human Mtb infection. In a mouse model of Mtb infection, IL-21 enhances immunogenicity of a DNA vaccine containing Ag85A (21).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, IL-21 correlates with vaccine efficacy272829, and following primary infection, M. tuberculosis -specific CD4 + T cells make IL-21 and frequently co-produce IFNγ, IL-2 and/or TNF30. A single study measured bacterial growth in IL-21 −/− mice following infection, and found comparable bacillary loads in WT and KO mice through day 200 post-infection31.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we argue that IL-21 acts as a ‘Signal 3’ cytokine and is important for initiation of the CD8 + T cell responses in the LN. In this way, IL-21 functions similarly to IL-12 by promoting early T cell proliferation and cytokine production3044.…”
Section: Discussionmentioning
confidence: 99%